Feasibility of postoperative adjuvant chemotherapy using carboplatin plus S-1 in completely resected non-small cell lung cancer patients. (18th August 2019) - Inoue, Masayoshi; Kusumoto, Hidenori; Shiono, Hiroyuki; Shintani, Yasushi; Ose, Naoko; Sakamaki, Yasushi; Okami, Jiro; Higashiyama, Masahiko; Takeuchi, Yukiyasu
Abstract : Feasibility is one of the major concerns during adjuvant chemotherapy in patients with completely resected non-small cell lung cancer. A phase II clinical trial of adjuvant chemotherapy with four courses of carboplatin (AUC 5 at day 1) and S-1 (80 mg/m 2 /day for 2 weeks followed by a 2-week rest) was performed to evaluate the feasibility (UMIN 9101). The primary endpoint was the completion rate and the secondary endpoints were adverse events, 2-year overall survival and disease-free rates. Thirty-five non-small cell lung cancer patients were enrolled. The adjuvant chemotherapy completion rate was 85.3% (29/34); 17/34 (50%) patients completed 4 courses without dose reduction. There were no treatment-related deaths, and Grade 3/4 adverse events included neutropenia (38.2%), leukocytopenia (14.7%), anemia (20.6%), thrombocytopenia (20.6%), anorexia (5.9%), fatigue (5.9%), and oral mucositis (2.9%). Two-year overall and disease-free survival rates were 96.3% and 53.3%, respectively. Adjuvant chemotherapy with carboplatin plus S-1 is safe and feasible.